Comparison of translational and rotational modes towards passive rheology of the cytoplasm of MCF-7 cells using optical tweezers - Roy, Srestha; Vaippully, Rahul; Lokesh, Muruga; Nalupurackal, Gokul; Edwina, Privita; Bajpai, Saumendra; Roy, Basudev (Frontiers in Physics, 2023)
A colloidal particle placed inside the cell cytoplasm is enmeshed within a network of cytoskeletal fibres immersed in the cytosolic fluid. The translational mode is believed to yield different rheological parameters than the rotational mode, given that these modes stretch the fibers differently. We compare the parameters for Michigan Cancer Foundation-7 (MCF-7) cells in this manuscript and find that the results are well comparable to each other. At low values of 0 Hz viscosity, the rotational and translational viscoelasticity matches well. However, discrepancies appear at higher values which may indicate that the cytoskeletal modes involved in rotation and translation of the particle are getting invoked.